THE ROLE OF LEGAL ASSISTANCE INSTITUTIONS IN PROVIDING LEGAL ASSISTANCE TO WOMEN AS VICTIMS OF SEXUAL VIOLENCE - Anita Damayanti (SEAN Institute, 2021)
The purpose of this study was to determine the legal assistance provided by LBH APIK to victims of sexual violence and the obstacles faced by LBH APIK in providing legal assistance to women victims of sexual violence. This research is a field research where data collection is carried out by interviewing parties related to the research topic. The results of the study show that: 1) The legal basis of the Indonesian Women's Association for Justice Legal Aid Institute or LBH APIK in providing legal assistance to women victims of violence is based on Law no. 16 of 2011 concerning Legal Aid, Law no. 18 of 2003 concerning Advocates and Standard Operating Procedures, hereinafter abbreviated as SOP. The role in providing legal assistance to women as victims is litigation and non-litigation. Litigation is a process of mentoring from the beginning of handling a case to a verdict in court, non-litigation is a process outside the court that is up to the mediation stage. In addition, LBH APIK carries out other legal reinforcements such as conducting legal counseling and legal seminars held in the Makassar city area. 2) The obstacles faced by LBH APIK in handling their cases are victims who are reluctant to tell their cases and the police who think that if there is sexual violence against women it is based on consensual factors, not coercion. LBH APIK carried out other legal reinforcements such as conducting legal counseling and legal seminars held in the Makassar city area. 2) The obstacles faced by LBH APIK in handling their cases are victims who are reluctant to tell their cases and the police who think that if there is sexual violence against women it is based on consensual factors, not coercion. LBH APIK carried out other legal reinforcements such as conducting legal counseling and legal seminars held in the Makassar city area. 2) The obstacles faced by LBH APIK in handling their cases are victims who are reluctant to tell their cases and the police who think that if there is sexual violence against women it is based on consensual factors, not coercion.